Fusional stamina: An alternative to Sheard’s criterion - Myklebust, Arnulf; Riddell, Patricia (Scandinavian Journal of Optometry and Visual Science, 2016)
Sheard postulated that symptoms from heterophoria can be avoided if the fusional reserves in the opposite direction are at least twice the size of the phoria itself; this is known as “Sheard’s criterion”. Although later studies have provided supporting evidence for this postulate, dichotomous criteria of this type are subject to a lack of sensitivity since small differences in measurements can result in a change in classification. The main purpose of this study was to provide a reliable continuous alternative measure to Sheard’s criterion in children; we have called this “Fusional Stamina”. Heterophorias and positive fusional vergence (PFV) were measured in a group of 82 typical children aged 5–11 years. The suggested new variable, fusional stamina, was calculated by dividing PFV by two and then subtracting the (hetero-) phoria. Repeatability at near was checked after one year for a subgroup of 40 children assumed to be at greater risk for binocular vision deficits. Mean fusional stamina was 8.1 PD (Prism Dioptres base out) (SD = ±5.9 PD) for distance and 12.3 PD (SD = ±8.2 PD) for near. Repeatability at near was r = 0.62, p < 0.001, compared to r = 0.38, p = 0.02 for PFV break-value. Five children passed Sheard’s criterion on only one of two repeated tests, but showed low fusional stamina on both tests. Normative values of fusional stamina for a group of typical children are presented. Repeatability for near is high and better than for PFV. Results demonstrate that there is a risk of missing binocular problems based only on passing Sheard’s criterion. The continuous alternative of fusional stamina can be useful for researchers as well as clinicians in quantifying binocular vision problems and to monitor the effects of treatment.